Al-Zamakhsari and the Miraculous Nature of Al-Qur'an - M. Amin Nurdin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 1999)
When al-Qur'an was sent down to the Arab people, the bigger part of them did believe in it, while some did not believe that it is the revelation from God. Among those who disbelieved they actually did kwon the i'jaz aspect of al-Qur'an. This was proved when they tried to match the eloquence of al-Qur'an, which then occurred to be a failure.